Pengembangan Layanan Penyebaran Informasi Akademik Berbasis Android - Gregorius Ferdian F.D.Setyawan; Hero Wintolo; Yuliani Indrianingsih (UIN Sunan Kalijaga Yogyakarta, 2018)
E-pengumuman is a multimedia-based information dissemination application that utilizes internet network as data eye media. The use of android mobile apps as a tool for accessing anything connected to the internet helps the customers with information submitted by the app site. Make the Internet as a central storage server to manage data as well as information. Services available on the application can be accessed through student information websites, faculty, and courses. While the news can be accessed via mobile Android. The results of this app testing show that this application can be used as a delivery service and receive information appropriately.